Development of light-transmitting concrete – A review. (2021) - Chiew, Shing Mei; Ibrahim, Izni Syahrizal; Sarbini, Noor Nabilah; Mohd Ariffin, Mohd Azree; Lee, Han Seung; Singh, Jitendra Kumar
Abstract: This paper provides an overview on the development of Light-transmitting Concrete (LTC). Concrete is improved in terms of transparency by installing optical fibres into the concrete. The application of LTC in building enables light transmission, which reduces light energy consumptions and carbon footprint, providing a more sustainable living environment. This paper also discusses the current development and application of LTC. Some of the previous research regarding the microstructure and mechanical properties of LTC in terms of compressive strength and light transmittance properties are also discussed. LTC has greater light transmittance with higher fibre volumetric fraction, smaller fibre diameter and spacing. However, the relationship between the factors and the light transmitting properties of LTC is yet to be investigated. Besides the fibre parameters, other environmental factors should also be considered to investigate the applicability and durability of LTC. There is still lack of investigation on the physical and mechanical properties of LTC especially in the applications for structural performance. Further research is required to investigate the fibre–matrix interfacial bond strength of LTC and measures should be taken to improve the mechanical strength of LTC. Besides buildings, there is also a research potential on the application of LTC on civil and infrastructure in terms of traffic safety.